The Intergalactic Design Guide Harnessing the Creative Potential of Social Design - Heller, Cheryl (Island Press/Center for Resource Economics, 2018)
"The Intergalactic Design Guide is a call for entries to design our way out of the civilization we have created, by using our collective creativity to change the human condition. Readers will come away transformed by the realization that we can use the invisible forces of social design to create a future where we live in a state of mutuality with one another and nature. This is one of the most critical design books of our time." Ivy Ross, Vice President of Google, Hardware Design "This book fills the cavernous gap between our awareness and understanding of 'design thinking' and 'design doing.' The first truly useful guide for those of us working to have impact, it shares numerous case studies of people and organizations that have transformed reality by combining the skills of thinking and acting in a design context. An absolute must-read for all of us looking to change the world in our own special ways!" Len Schlesinger, Baker Foundation Professor, Harvard Business School; President Emeritus, Babson College "There are design problems and there are human problems. Cheryl Heller's genius is to see them as one and the same with the goal of building human capacity, not just buildings. This is the framework for designing the design process." David W. Orr, Paul Sears Distinguished Professor Emeritus, Oberlin College.